Process-Genre Approach for Teaching Writing of English Text - Dedi Jasrial (English Education Study Program Faculty of Teacher Training and Education, 2019)
Although writing has been learned by students since they start to learn English language but it still become the most difficult skill to be acquired than speaking, reading and listening. It is possibility caused by the students have limitation of knowledge about writing roles, lack of vocabulary, lack of motivation, lack of master of language structure, and lack of ability in generating a topic. In addition, writing is also called as the most complexity skill and it can be seen from the process of writing, rules that must be followed by students, and the influence of non-linguistics factors during of writing activity. Therefore, students must be serious to acquire this skill. In this article, the writer would like to introduce a suitable approach to teaching writing of English texts through process-genre approach. After reading this article, the writer expects that this article can help English teachers to apply this approach for teaching writing of English texts at Junior and Senior High Schools in Indonesia.